Diagnostic Accuracy of Computed Tomography and Clinical Examination in the Assessment of Mandibular Invasion of Oral Squamous Cell Carcinomas - Md Ikbal Hosen; Kawsar Jahanara Akther; A F M Shakilur Rahman; Md Ali Hossain Talukdar; Tamanna Zahur; Md Jakirul Islam; Ismat Ara Haider (Update Dental College, 2024)
Introduction: Computed tomography (CT) scan precisely shows soft and hard tissues in the same test hereby determines the lesion extension, involvement of regional node as well as of bone. Current study was aimed to evaluate the efficacy of clinical examination and CT to assess mandibular invasion in oral squamous cell carcinoma. Materials and methods: This cross-sectional study was conducted at Dhaka Dental College Hospital from July, 2016 to July, 2017 among conveniently selected 35 patients of histologically confirmed squamous cell carcinoma which was close to the mandible. The patients underwent proper clinical examination. CT scan was performed; preoperative staging and treatment plan was formulated according to the status of bone invasion. After mandibulectomy, the resected specimens were sent for histopathology. The findings from clinical examination and CT were then correlated with the gold standard, postoperative histopathology. Results: Clinical examination accurately detected 22 cases to have bone invasion and 8 cases with no bone invasion. It also gave 2 false positive and 3 false negative results. On the other hand CT accurately detected 24 cases to have bone invasion and 9 cases with no bone invasion. It provided one false positive and one false negative result. However, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of clinical examination were 88%, 80%, 91.67%, 72.73%, 85.71% respectively (p = 0.0002) and of CT were 96%, 90%, 96%, 90%, 94.28% respectively (p < 0.0001). Clinical examination and CT were found sensitive enough and have an acceptable range of specificity as primary investigative modalities. CT scan outperforms clinical examination in terms of sensitivity, specificity, NPV, and accuracy. Conclusion: CT scan imaging is the method of choice for planning treatment in advanced oral squamous cell carcinoma. This study reveals how a CT scan can provide additional diagnostic value to detect bone invasion. Update Dent. Coll. j: 2024; 14(2): 21-26